(untitled) (European Bison Conservation Newsletter, 2016)
Until now in Spain reported were 6 confirmed cases and 1 uncertain of male balanopostitis in European bison. Four cases were diagnosed on the basis of symptoms and confirmed in necropsy while 2 cases were diagnosed basing on symptoms, animals were treated and both are still alive. An animal classified as an uncertain case also remains alive. Four of diagnosed European bison originated from the Lowland line, and 2 from Lowland – Caucasian line. All those individuals were imported to Spain from abroad. So far no E. bison born in Spain has been infected.